2001
DOI: 10.1111/j.1572-0241.2001.04048.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic therapy of acute diverticular hemorrhage

Abstract: Endoscopic therapy can provide early hemostasis in some cases of acute diverticular hemorrhage. However, its value in preventing subsequent diverticular bleeding is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 17 publications
0
63
1
1
Order By: Relevance
“…However, no early or delayed recurrence (after a median follow-up of 2 years) took place in the patients who underwent endoscopic haemostatic treatment with epinephrine injection and/or bipolar coagulation, a statistically significant difference. However in another study, 38% of the patients experienced recurrent bleeding after endoscopic haemostasis [73]. Endoscopic treatment may modify the natural history of diverticular bleeding by preventing recurrences, but its role has to be further clarified in larger studies with longer follow-up periods.…”
Section: Clinical Picturementioning
confidence: 99%
“…However, no early or delayed recurrence (after a median follow-up of 2 years) took place in the patients who underwent endoscopic haemostatic treatment with epinephrine injection and/or bipolar coagulation, a statistically significant difference. However in another study, 38% of the patients experienced recurrent bleeding after endoscopic haemostasis [73]. Endoscopic treatment may modify the natural history of diverticular bleeding by preventing recurrences, but its role has to be further clarified in larger studies with longer follow-up periods.…”
Section: Clinical Picturementioning
confidence: 99%
“…However, in their study, only five patients had active bleeding and five patients had a nonbleeding visible vessel. In a retrospective review by Bloomfeld et al of 13 patients presenting with acute lower GIB who underwent endoscopic therapy using IE and/or CTC, five (39%) experienced recurrent bleeding (within 30 days of the index bleed), four of whom required surgical intervention [13]. In a prospective study by Green et al, where patients were randomized to urgent colonoscopy or standard care, ongoing bleeding was suspected in 27 of 50 (54%) patients randomized to urgent colonoscopy.…”
Section: Discussionmentioning
confidence: 96%
“…Some reports have indicated that Western countries usually performed thermal contact therapy[18,26,28,29]; however, this therapy is not approved in Japan[30]. Several reports from Western countries showed that clipping was a useful hemostasis treatment[12,31,32], and clipping may be performed as a common endoscopic treatment for CDB patients.…”
Section: Discussionmentioning
confidence: 99%